2015
DOI: 10.33800/nc.v0i8.39
|View full text |Cite
|
Sign up to set email alerts
|

The tadpoles of the hylid frogs (Anura: Hylidae: Hypsiboas and Osteopilus) of Hispaniola

Abstract: Hispaniolan hylid frogs are represented by four endemic species: Hypsiboas heilprini, Osteopilus dominicensis, O. pulchrilineatus and O. vastus. There are two tadpole ecomorphs represented in the hylid frogs of Hispaniola: lentic (O. dominicensis and O. pulchrilineatus) and lotic (H. heilprini and O. vastus). Tadpoles of the four species may be found sympatrically, but in different microhabitats. Hispaniolan hylid tadpoles reach a moderate size (up to 57 mm in total length is recorded in H. heilprini), and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Ron et al, 2012; Jungfer et al, 2013). Regarding the latter, Noble (1927) and Díaz et al (2015) reported, however, that eggs are laid in water retained in basins in gravel and stone on the edge of a pond in a stream; six days after hatching, larvae move over wet stones to the stream, where they complete their development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ron et al, 2012; Jungfer et al, 2013). Regarding the latter, Noble (1927) and Díaz et al (2015) reported, however, that eggs are laid in water retained in basins in gravel and stone on the edge of a pond in a stream; six days after hatching, larvae move over wet stones to the stream, where they complete their development.…”
Section: Discussionmentioning
confidence: 99%
“…Juncá et al (2008) reported on the larvae of Corythomantis , which have a number of character states that are likely autapomorphies of this genus. These include the absence of an anterior gap in the marginal papillae of the oral disc (in Lophyohylini, homoplastic in Osteocephalus festae and Osteopilus vastus ; Ron et al, 2010; Galvis et al, 2014; Díaz et al, 2015); the occurrence of at least five anterior tooth rows (vs. a maximum of four in all known larvae of Itapotihyla , Nyctimantis and Trachycephalus ; Schiesari et al, 1996; Schiesari and Moreira, 1996; Wogel et al, 2000, 2006; Prado et al, 2003; Pimenta and Canedo, 2007; Cajade et al, 2010); and the enlarged oral disc, whose maximum width is ca. 80% of maximum body width (vs. 50–66% in the other species of Lophyohylini having large oral discs, Osteopilus vastus , O. pulchrilineatus and Osteocephalus festae ; Ron et al, 2010; Galvis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations